Implementasi E-booklet Interaktif untuk Meningkatkan Kemampuan Analisis Siswa Kelas VIII pada Mata Pelajaran IPS Terpadu di SMP Negeri 1 Gunungsitoli - Kornelia Candraria Ndruru; Eka Septianti Laoli; Arianto Lahagu; Yearning Harefa (Jurnal Tematik, 2025)
The purpose of this study is to determine the implementation of interactive e-booklets in learning and interactive can improve the analytical skills of class VIII students in Integrated Social Studies subjects at SMP Negeri 1 Gunungsitoli. This study is a Classroom Action Research that contains a research flow that includes four stages, starting from planning, implementation of actions, observation and reflection. The four stages take place in 2 cycles. The research instruments are teacher and student observation sheets, learning outcome tests and documentation. The subjects of this study were 32 class VIII-I students of SMP Negeri 1 Gunungsitoli. Based on the results of this study it is known that: (1) The results of observations for teachers in cycle I reached an average of 56.24%, while in cycle II the teacher's ability in implementing the learning process increased to 85.71%. The results of observations of student activities in cycle II reached an average of 49.21% and in cycle II reached an average of 86.06%; (2) In cycle I the average student learning outcomes were 72.40 while in cycle II the average student learning outcomes were 85.31; (3) The percentage of completion achieved in cycle I was 46.87% while the percentage of completion in cycle II was 93.75%, which is proven to increase students' analytical abilities and student activities in the learning process. The increase in students' analytical abilities and activities in the learning process means that it will have an impact on learning outcomes which will also increase.